Geochemistry, sulfur and lead isotopic composition of hydrothermal sulfide from the Duanqiao hydrothermal field on the Southwest Indian Ridge: implications for ore genesis - Yang, Weifang; Liao, Shili; Alveirinho Dias, Ágata; Liang, Jin; Li, Wei; Ding, Teng; Tao, Chunhui (International Geology Review, 2022)
Hydrothermal activities on ultraslow-spreading ridges exhibit diverse characteristics, long histories with multiple participants, and might form large-scale, high-grade sulfide deposits. The Duanqiao hydrothermal field (DHF) is located at the segment with the thickest oceanic crust and a large axial magma chamber on the Southwest Indian Ridge, providing unique perspective of sulfide metallogenesis on ultraslow-spreading ridges. Previous studies revealed that DHF sulfide exhibits distinct features of enrichment of ore-forming elements in comparison with those of hydrothermal fields on sediment-starved mid-ocean ridges. However, the genesis and processes responsible for such differences remain poorly constrained. In this study, mineralogical, geochemical and S and Pb isotopic analyses were performed on relict sulfide mound samples to characterize DHF formation. The samples show clear concentric mineral zonation from the interior to the exterior wall. Assemblages of chalcopyrite, sphalerite, and pyrite are distributed mainly in the interior wall, whereas pyrite and marcasite are distributed mainly in the exterior wall. The low Cu content and Pb isotopic composition of the sulfide indicate that the metals are derived mainly from basement basalts. The δ34S values exhibit positive values distributed over a reasonably narrow range (2.42‰–7.97‰), which suggests approximately 62.1%–88.5% of S with basaltic origin. Compared with most hydrothermal fields along the sediment starved mid-ocean ridges, the DHF sulfide shows particularly high contents of Pb (263–2630 ppm), As (234–726 ppm), Sb (7.32–44.3 ppm), and Ag (35.2 to >100 ppm). The δ34S values exhibit an increasing tendency from the sample exterior to the interior. We propose that these features probably reflect the existence of a subsurface zone refining process. Our results provide new insight into the sulfide formation process and contribute to understanding the metallogenic mechanism of hydrothermal sulfides on ultraslow-spreading ridges.
Publisher: Taylor & Francis _eprint: https://doi.org/10.1080/00206814.2022.2081937
Keywords: Hydrothermal sulfide; geochemistry; southwest Indian ridge; sulfur isotope; zone refining

A touristic habitation: automobilities of Chinese driving tourists - Yang, Peng; Xu, Honggang; Hannam, Kevin (Tourism Geographies, 2022)
As an emergent tourism sector, driving tourism connects car use and touristic activities intimately. Following the notion of the ‘inhabited car’, this article explores how and why Chinese tourists inhabit a travelling car for drivers/passengers in the leisure automobility and driving tourism context. Through three different road trips and ‘mobile methods’, it was found that Chinese tourists inhabit the car in four ways: driving, gazing, listening, and communicating. Through this embodied habitation, the car is turned into a ‘touristic inhabitation’ space for protecting the tourists generating touristic emotions、social interactions, and tourism meanings. The study contributes to automobility and tourism literature and provides implications for driving tourism development in China.
Publisher: Routledge _eprint: https://doi.org/10.1080/14616688.2022.2046148
Keywords: Automobilities; China; cars; driving tourism; habitation

Multi-Branch-CNN: Classification of ion channel interacting peptides using multi-branch convolutional neural network - Yan, Jielu; Zhang, Bob; Zhou, Mingliang; Kwok, Hang Fai; Siu, Shirley W. I. (Computers in Biology and Medicine, 2022)
Ligand peptides that have high affinity for ion channels are critical for regulating ion flux across the plasma membrane. These peptides are now being considered as potential drug candidates for many diseases, such as cardiovascular disease and cancers. In this work, we developed Multi-Branch-CNN, a CNN method with multiple input branches for identifying three types of ion channel peptide binders (sodium, potassium, and calcium) from intra- and inter-feature types. As for its real-world applications, prediction models that are able to recognize novel sequences having high or low similarities to training sequences are required. To this end, we tested our models on two test sets: a general test set including sequences spanning different similarity levels to those of the training set, and a novel-test set consisting of only sequences that bear little resemblance to sequences from the training set. Our experiments showed that the Multi-Branch-CNN method performs better than thirteen traditional ML algorithms (TML13), yielding an improvement in accuracy of 3.2%, 1.2%, and 2.3% on the test sets as well as 8.8%, 14.3%, and 14.6% on the novel-test sets for sodium, potassium, and calcium ion channels, respectively. We confirmed the effectiveness of Multi-Branch-CNN by comparing it to the standard CNN method with one input branch (Single-Branch-CNN) and an ensemble method (TML13-Stack). The data sets, script files to reproduce the experiments, and the final predictive models are freely available at https://github.com/jieluyan/Multi-Branch-CNN.
3 citations (Crossref) [2022-09-21]
Keywords: Classification; Deep learning; Drug discovery; Ion channel; Multi-Branch-CNN; Peptides

Recent Progress in the Discovery and Design of Antimicrobial Peptides Using Traditional Machine Learning and Deep Learning - Yan, Jielu; Cai, Jianxiu; Zhang, Bob; Wang, Yapeng; Wong, Derek F.; Siu, Shirley W. I. (Antibiotics, 2022)
Antimicrobial resistance has become a critical global health problem due to the abuse of conventional antibiotics and the rise of multi-drug-resistant microbes. Antimicrobial peptides (AMPs) are a group of natural peptides that show promise as next-generation antibiotics due to their low toxicity to the host, broad spectrum of biological activity, including antibacterial, antifungal, antiviral, and anti-parasitic activities, and great therapeutic potential, such as anticancer, anti-inflammatory, etc. Most importantly, AMPs kill bacteria by damaging cell membranes using multiple mechanisms of action rather than targeting a single molecule or pathway, making it difficult for bacterial drug resistance to develop. However, experimental approaches used to discover and design new AMPs are very expensive and time-consuming. In recent years, there has been considerable interest in using in silico methods, including traditional machine learning (ML) and deep learning (DL) approaches, to drug discovery. While there are a few papers summarizing computational AMP prediction methods, none of them focused on DL methods. In this review, we aim to survey the latest AMP prediction methods achieved by DL approaches. First, the biology background of AMP is introduced, then various feature encoding methods used to represent the features of peptide sequences are presented. We explain the most popular DL techniques and highlight the recent works based on them to classify AMPs and design novel peptide sequences. Finally, we discuss the limitations and challenges of AMP prediction.
Number: 10 Publisher: Multidisciplinary Digital Publishing Institute
Keywords: antimicrobial peptide; classification; deep learning; machine learning; medicine; regression; therapeutic peptide

The effect of time regime in noise exposure on the auditory system and behavioural stress in the zebrafish - Wong, Man Ieng; Lau, Ieng Hou; Gordillo-Martinez, Flora; Vasconcelos, Raquel O. (Scientific Reports, 2022)
Anthropogenic noise of variable temporal patterns is increasing in aquatic environments, causing physiological stress and sensory impairment. However, scarce information exists on exposure effects to continuous versus intermittent disturbances, which is critical for noise sustainable management. We tested the effects of different noise regimes on the auditory system and behaviour in the zebrafish (Danio rerio). Adult zebrafish were exposed for 24 h to either white noise (150 ± 10 dB re 1 μPa) or silent control. Acoustic playbacks varied in temporal patterns—continuous, fast and slow regular intermittent, and irregular intermittent. Auditory sensitivity was assessed with Auditory Evoked Potential recordings, revealing hearing loss and increased response latency in all noise-treated groups. The highest mean threshold shifts (c. 13 dB) were registered in continuous and fast intermittent treatments, and no differences were found between regular and irregular regimes. Inner ear saccule did not reveal significant hair cell loss but showed a decrease in presynaptic Ribeye b protein especially after continuous exposure. Behavioural assessment using the standardized Novel Tank Diving assay showed that all noise-treated fish spent > 98% time in the bottom within the first minute compared to 82% in control, indicating noise-induced anxiety/stress. We provide first data on how different noise time regimes impact a reference fish model, suggesting that overall acoustic energy is more important than regularity when predicting noise effects.
0 citations (Crossref) [2022-09-21] Number: 1 Publisher: Nature Publishing Group
Keywords: Ecology; Neuroscience; Physiology; Zoology

Measuring Specific Traditional Chinese Values in Relation to Satisfaction of the Five Maslow Needs - Taormina, Robert J.; Gao, Jennifer H.; Kuok, A. C.H. (Psychological Thought, 2022)
To determine whether living according to specific traditional Chinese cultural values was associated with satisfaction of the five needs in Maslow’s motivational hierarchy and overall life satisfaction, a mixed-method approach was employed, with an empirical questionnaire and supplemental interviews. The questionnaire assessed the hypothesized relationships that traditional Chinese values had with personal life outcomes, including health, employment, satisfaction of the five needs from Maslow’s hierarchy, and life satisfaction. The interviews examined the relationships that several demographic variables had with living by traditional Chinese values. The results of the empirical data revealed that most Chinese people today are still living according to the traditional Chinese cultural values, and that living by those traditional values are strongly associated with satisfaction of all five of the human needs in the Maslow hierarchy, as well as with overall life satisfaction. Additionally, the results of the qualitative interviews readily supported the empirical findings, and also revealed that the time during which inter-generational transmission of the Chinese cultural values occurs is when parents teach those values to their children at a very early age, that is, between 3 and 8 years old, before the children start primary school.
0 citations (Crossref) [2022-10-30]

Mangrove Conservation in Macao SAR, China: The Role of Environmental Education among School Students - Tagulao, Karen Araño; Bernardo, Allan B. I.; Kei, Loi Hoi; Calheiros, Cristina Sousa Coutinho (International Journal of Environmental Research and Public Health, 2022)
Mangrove forests are one of the most ecologically valuable ecosystems in the world and provide a wide variety of ecosystem services to coastal communities, including cities. Macao, a highly urbanized coastal city located on the southern coast of China west of the Pearl River, is home to several species of mangroves with many associated flora and fauna. Mangrove forests in Macao are vulnerable to threats due to pressure from rapid and massive urban developments in the area, which led to mangrove loss in the past decades. To address this issue, the local authorities established special Ecological Zones for the management of the local mangroves. To reinforce local conservation efforts, educating the local population about the value of mangroves, especially school students, is of utmost importance. To evaluate the impact of environmental education activities on the environmental orientation, knowledge, and values of students toward mangrove conservation in Macao, a quasi-experimental study was undertaken. The effectiveness of a mangroves exhibition and field visit were evaluated using the New Environmental Paradigm (NEP) Scale—Macao version in a group of local school students who participated in the activities. Overall, the results provided consistently positive evaluations of the impact of the environmental education program. The strongest improvements were found in the students’ pro-environmental orientations, knowledge about mangroves, and value for environmental protection.
0 citations (Crossref) [2023-03-15] Number: 6 Publisher: Multidisciplinary Digital Publishing Institute
Keywords: NEP-New Ecological Paradigm; conservation; environmental orientation; environmental protection; urban mangroves

La terre des autochtones potiguara du brésil: une construction sociale et politique - Simões, José Manuel (E-Journal of Intercultural Studies, 2022)
The land of the potiguara indians of Brazil: a social and political construction The space in which the potiguaras of Brazil live is, today as in the past, the result of a longterm process, many negotiations and well-managed refuges. Paradoxically, despite their recurrent discourse invoking the ancestry of their lands of origin, the Potiguara fight and continue to fight politically for the return to the spaces where their colonial refuge took place.

Selection for winners impacts the endocrine system in the Siamese fighting fish - Ramos, A.; Gonçalves, D. (General and Comparative Endocrinology, 2022)
In southeast Asia, males of the Siamese fighting fish, Betta splendens, have been selected across centuries for winning paired staged fights and previous work has shown that males from fighter strains are more aggressive than wild-types. This strong directional selection for winners is likely to have targeted aggression-related endocrine systems, and a comparison between fighter and wild-type strains can bring into evidence the key hormones implicated in aggression. Here, we compared the plasma levels of the androgen 11-ketotestosterone (KT) and of the corticosteroid cortisol (F) in F2 males of a fighter and a wild-type strain raised under similar laboratory conditions. We show that F was generally lower in fighter as compared with wild-type males, while no overall differences in KT levels were detected between strains. When presented with a mirror-induced aggressive challenge, post-fight levels of F increased but more significantly so in wild-type males, while KT increased in males of both strains. After the challenge, fighter males had higher levels of KT as compared with wild-type males, while the pattern for F was opposite. As compared with animals in social groups, wild-type males placed under social isolation had lower F levels, while KT decreased for fighters. Taken together, this data suggests that while wild-type males responded to aggression with an increase in circulating levels of both androgens and corticosteroids, males selected for winning fights maintained a blunt F response, increasing only KT levels. These data agree with the hypothesis that a combination of high levels of androgens and low levels of corticosteroids is associated with high aggression. Overall, these results seem to indicate that selection for winning had a stronger impact in the hypothalamus-pituitary-interrenal axis than in the hypothalamus-pituitary–gonadal axis in B. splendens.

Material Source of Sediments from West Clarion–Clipperton Zone (Pacific): Evidence from Rare Earth Element Geochemistry and Clay Minerals Compositions - Qiu, Zhongrong; Tao, Chunhui; Ma, Weilin; Dias, Ágata Alveirinho; Hu, Siyi; Shao, Yuexiao; Yang, Kehong; Zhang, Weiyan (Journal of Marine Science and Engineering, 2022)
The geochemistry and mineralogy of sediments provide relevant information for the understanding of the origin and metallogenic mechanism of ferromanganese nodules and crusts. At present, there are still few studies on the sediment origin of the Clarion–Clipperton Zone (CCZ) of the east Pacific, particularly on the systematic origin of sediments with a longer history/length. Here, bulk sediment geochemistry and clay mineral compositions were analyzed on a 5.7 m gravity core (GC04) obtained at the CCZ, an area rich in polymetallic nodules. The results indicate that the average total content of rare earth elements (REE), including yttrium (REY), in sediments is 454.7 ppm and the REEs distribution patterns normalized by the North American Shale Composite of samples are highly consistent, with all showing negative Ce anomalies and more obvious enrichment in heavy REE (HREE) than that of light REE (LREE). Montmorillonite/illite ratio, discriminant functions and smear slide identification indicate multiple origins for the material, and are strongly influenced by contributions from marine biomass, while terrestrial materials, seamount basalts and their alteration products and authigenic source also make certain contributions. The REY characteristics of the sediments in the study area are different from those of marginal oceanic and back-arc basins, and more similar to pelagic deep-sea sediments. Based on LREE/HREE-1/δCe and LREE/HREE-Y/Ho diagrams, we conclude that samples from the study area had pelagic sedimentary properties which suffered from a strong “seawater effect”.
Number: 8 Publisher: Multidisciplinary Digital Publishing Institute
Keywords: Clarion–Clipperton Zone; material source; rare earth elements; sediments geochemistry

In Memorial and Serenity: Introducing VR Grave Mourning in the Chapel of St. Michael in Macao - Olga Ng Ka Man, Sandra; Caires, Carlos Sena (International Journal of Creative Interfaces and Computer Graphics, 2022)
Macao inhabit a population of 683,100. The birth rate has been dropping while the death rate has risen compared to two years ago. Cemeteries are becoming crowded, and burial spots are demanding. In this case, video calls and social media can be the solution. How about our beloved ancestors? Can we video call them on their memorial days? This paper presents a VR experience of immersing oneself in the 3D VR of the Chapel of St. Michael of Macao to create a peaceful atmosphere for grave mourning. The chapel is also a personal space where we can be truly isolated in serenity. It is a retreat to pray, disconnect, and reconnect to the beloved deaths that may not be buried in an easily accessible location. The authors propose a possible future of mourning our loved ones through virtual reality and telepresence: an immersive experience connected with Macao's extraordinary and cultural unicity.

The Emergence of Resources Seeking Chinese Firms’ Specific Advantages in Emerging Market - Ojo, Olukayode Iwaloye; Im, Hong Kei; Adeniyi, Damilola Olarewaju; Gbadamosi, Ayantunji; Alves, Jose; Link to external site, this link will open in a new window; Trimarchi, Michael (Sustainability, 2022)
It is argued that the role of the Chinese government to support the cross-border operations of Chinese firms is to assist these firms in overcoming their limited established brands, and their disadvantages in technology and managerial resources, which were also the reasons why such firms decided to enter emerging markets instead of developed markets. This strategic choice is preferred to avoid direct confrontation with established firms from developed countries endowed with superior ownership advantages. Therefore, Chinese resources seeking firms innovate by increasing investment in developing and emerging markets to develop unique ownership advantages for sustainable market development and competitive advantage. This research investigates the ownership advantages of resources seeking Chinese firms in these markets using the OLI theory. The paper contributes to explaining the specific advantages of Chinese MNEs when entering emerging markets. The study applied a two-stage qualitative methodology to examine Chinese firms operating in Nigeria. The first stage included an exploratory study based on interviews with key informants and experts while the second stage included a case study methodology. The study focused on resources seeking Chinese MNEs operating in Nigeria.
Num Pages: 8345 Place: Basel, Switzerland Publisher: MDPI AG
Keywords: OLI theory and Chinese firms; emerging markets; ownership advantages; resources seeking MNEs

Conceptual replications, research, and the “what works” agenda in education - Morrison, Keith (Educational Research and Evaluation, 2022)
2 citations (Crossref) [2022-09-21]

Going to Church in Medieval England by Nicholas Orme (review) - Morgan, Stephen (Antiphon: A Journal for Liturgical Renewal, 2022)
0 citations (Crossref) [2023-01-27] Publisher: The Catholic University of America Press

The Fire “Once Kindled on Moriah”: Wojtyła and Newman on the Conditions for the Proposal of Christ - Morgan, Stephen (Newman Studies Journal, 2022)
0 citations (Crossref) [2023-01-27] Publisher: The Catholic University of America Press

Ockham on the Side of the Angels: Why a Classical Theist Shouldn't be Moved by Oppy's Argument from Simplicity - McNabb, Tyler; DeVito, Michael (New Blackfriars, 2022)
0 citations (Crossref) [2022-09-21]

Cognitive Science of Religion and Classical Theism: A Synthesis - McNabb, Tyler Dalton; DeVito, Michael (Religions, 2022)
Launonen and Mullins argue that if Classical Theism is true, human cognition is likely not theism-tracking, at least, given what we know from cognitive science of religion. In this essay, we develop a model for how classical theists can make sense of the findings from cognitive science, without abandoning their Classical Theist commitments. We also provide an argument for how our model aligns well with the Christian doctrine of general revelation.
0 citations (Crossref) [2022-09-21]

Climate Alarmism or Lukewarming? How So-Called American Conservatives Should Think About Climate Change - McNabb, T. D; Devito, M (Ethics & the Environment, 2022)
In this essay we argue that, based on current scientific data, the most prudential course of future actions that an American conservative can take, is one that assumes what we call climate change alarmism. In order to establish this thesis, we first provide a basic overview of the relevant climate change science, as well as give an analysis of the alarmist and lukewarming dialectic (the two primary interpretations of the data). We then move to develop our environmental wager. Finally, following Roger Scruton, we end this work by proposing what sort of policies conservatives should endorse going further.

Multimodal Game Design Framework for Creativity in Macau's Educational System Through Digital and Tangible Games: Chinese, Portuguese, and English Languages - Martins de Abreu, F.; Barbosa, Álvaro Mendes (International Journal of Creative Interfaces and Computer Graphics (IJCICG), 2022)
Creativity and collaboration are crucial to learning development in today's fast-paced educational environment. New technology can bridge humans and their natural needs through immersion in digital environments with physical objects. As knowledge and information evolve, digital interactive experienc...
Publisher: IGI Global

Understanding of base-10 concept and its application: a cross-cultural comparison between Japan and Singapore - Marcruz, Ong Yew Lee; Carrie, Ho Ka Lee; Manabu, Kawata; Mayumi, Takahashi; Kumpei, Mizuno (International Journal of Early Years Education, 2022)
It has become increasingly clear that the early use of decomposition for addition is associated with later mathematical achievement. This study examined how younger children execute a base-10 decomposition strategy to solve complex arithmetic (e.g. two-digit addition). 24 addition problems in two modalities (WA: Written Arithmetic; OA: Oral Arithmetic) with sums less than 100 were administered to 22 Japanese and 22 Singaporean 6-year-old kindergarteners. Our findings reveal that they were able to solve complex addition. For instance, Japanese kindergarteners tended to solve complex arithmetic using base-10 decomposition across the modality, whereas Singaporean kindergarteners used standard algorithms and basic counting to solve complex WA and OA problems, respectively. We speculate that Japanese kindergarteners might have a clearer understanding of the base-10 concept and were able to use this knowledge more readily than Singaporean kindergarteners. Mathematical experiences in kindergarten and number-naming systems have been put forward as two of the crucial contributors for such cross-cultural differences. This study also provides new directions for future research on the understanding of the base-10 concept and its application among young children.
Publisher: Routledge _eprint: https://doi.org/10.1080/09669760.2020.1848525
Keywords: Base-10 concept; decomposition strategy; kindergarten; mathematical experiences; number-naming system

Message from Program Chairs - Ma, J.; Du, W.; Lu, W. (Proceedings - 2022 IEEE/ACIS 22nd International Conference on Computer and Information Science, ICIS 2022, 2022)
ISBN: 9781665494632

Trying a board game intervention on children with autism spectrum disorder in Macau: how do they react? - Lok, Ka Ieong; Chiang, Hsu-Min; Lin, Yueh-Hsien; Jiang, Chunlian (International Journal of Developmental Disabilities, 2022)
Limited special education and related services are available for children with autism spectrum disorder (ASD) in Macau, especially those who are educated in general education classrooms. No intervention study has been conducted on these children. This study was conducted to explore the relationship between a board game play intervention and board game play behaviors and social communication of children with ASD educated in general education classrooms in Macau. A repeated measures design was used and the results of this study showed the mean occurrence of unprompted board game play behaviors per session during intervention was not significantly different from that during pre- or post-intervention. The mean occurrence of social communication per session during intervention was significantly higher than that during pre- and post-intervention. These findings suggest a positive relationship existed between the board game intervention used in this study and social communication of children with ASD.
Publisher: Taylor & Francis _eprint: https://doi.org/10.1080/20473869.2022.2095861
Keywords: Autism Spectrum Disorder; Macau; board game; play; social communication

A metamorphic devolatilization model for the genesis of the Baiyun gold deposit in the North China Craton: A novel Fe-S isotopes perspective - Liu, Shuaijie; Chen, Bin; Zheng, Jiahao; Wu, Yafei; Bao, Chuang; Zhao, Guochun (Gondwana Research, 2022)
The Mesozoic gold deposits in the North China Craton (NCC) were hosted by the Precambrian basement and Mesozoic intrusions. Thus, most researchers consider that these gold deposits were genetically linked to the Mesozoic intrusions. However, we suggest that a metamorphic devolatilization model provides an alternative based on a combined Fe and in-situ S isotopes study on auriferous pyrites from the Baiyun gold deposit in the NCC. The Triassic Baiyun gold deposit contains the quartz vein and altered rock ores that were developed in the Paleoproterozoic metavolcanic-sedimentary rocks (the Liaohe Group). Our in-situ S isotopic analyses show that pyrites from the quartz vein ores are characterized by negative δ34S values (-10.7 ∼ -5.5‰), while those from the altered rock ores have two distinct groups of δ34S values, one being positive (+13.5 ∼ +16.2‰) and the other negative (-10.6 ∼ -3.0‰). We suggest that pyrite grains with positive δ34S values should be relicts from the host rocks, because they show comparable δ34S values with those from the host rocks schists (+3.3 ∼ +16.1‰). Thus, only the negative δ34S values of pyrites in ores (-10.7 ∼ -3.0‰) and the Fe isotopes of the quartz vein ores (δ56Fe = +0.30 ∼ +0.48‰) can represent the isotopic characteristics of ore-forming fluids at Baiyun. Our study shows that the sulfur were probably from the pyritic volcanic-sedimentary sequences of the Liaohe Group, rather than from magmas. The calculated δ56Fe values of the ore-forming fluids (-0.78 ∼ -0.37‰; pyrite-fluid isotope fractionation) could be modelled in a metamorphic devolatilization model with Fe-species (pyrite&magnetite) of the Liaohe Group as sources. Therefore, our combined S- and Fe- isotope data indicate that the metamorphic devolatilization of the Liaohe Group could account for the genesis of the Baiyun gold deposit.
Keywords: Baiyun gold deposit; Fe isotope; Metamorphic devolatilization model; Orogenic gold deposits; S isotope

A Deep Neural Network Based on Circular Representation for Target Detection - Lin, Cong; Chen, Zhoujian; Huang, Yiquan; Jiang, Haoyu; Du, Wencai; Chen, Qiong (Journal of Sensors, 2022)
Convolutional neural network (CNN) model based on deep learning has excellent performance for target detection. However, the detection effect is poor when the object is circular or tubular because most of the existing object detection methods are based on the traditional rectangular box to detect and recognize objects. To solve the problem, we propose the circular representation structure and RepVGG module on the basis of CenterNet and expand the network prediction structure, thus proposing a high-precision and high-efficiency lightweight circular object detection method RebarDet. Specifically, circular tubular type objects will be optimized by replacing the traditional rectangular box with a circular box. Second, we improve the resolution of the network feature map and the upper limit of the number of objects detected in a single detect to achieve the expansion of the network prediction structure, optimized for the dense phenomenon that often occurs in circular tubular objects. Finally, the multibranch topology of RepVGG is introduced to sum the feature information extracted by different convolution modules, which improves the ability of the convolution module to extract information. We conducted extensive experiments on rebar datasets and used AB-Score as a new evaluation method to evaluate RebarDet. The experimental results show that RebarDet can achieve a detection accuracy of up to 0.8114 and a model inference speed of 6.9 fps while maintaining a moderate amount of parameters, which is superior to other mainstream object detection models and verifies the effectiveness of our proposed method. At the same time, RebarDet’s high precision detection of round tubular objects facilitates enterprise intelligent manufacturing processes.
0 citations (Crossref) [2022-09-21]

Hydrothermal remobilization of subseafloor sulfide mineralization along mid-ocean ridges contributes to the global oceanic zinc isotopic mass balance - Liao, Shili; Tao, Chunhui; Wen, Hanjie; Yang, Weifang; Liu, Jia; Jamieson, John W.; Dias, Ágata Alveirinho; Zhu, Chuanwei; Liang, Jin; Li, Wei; Ding, Teng; Li, Xiaohu; et al. (Geochimica et Cosmochimica Acta, 2022)
Hydrothermal activity on mid-ocean ridges is an important mechanism for the delivery of Zn from the mantle to the surface environment. Zinc isotopic fractionation during hydrothermal activity is mainly controlled by the precipitation of Zn-bearing sulfide minerals, in which isotopically light Zn is preferentially retained in solid phases rather than in solution during mineral precipitation. Thus, seafloor hydrothermal activity is expected to supply isotopically heavy Zn to the ocean. Here, we studied sulfide-rich samples from the Duanqiao-1 hydrothermal field, located on the Southwest Indian Ridge. We report that, at the hand-specimen scale, late-stage conduit sulfide material has lower δ66Zn values (−0.05 ± 0.15 ‰; n = 19) than early-stage material (+0.13 ± 0.15 ‰; n = 10). These lower values correlate with enrichments in Pb, As, Cd, and Ag, and elevated δ34S values. We attribute the low δ66Zn values to the remobilization of earlier sub-seafloor Zn-rich mineralization. Based on endmember mass balance calculations, and an assumption of a fractionation factor (αZnS-Sol.) of about 0.9997 between sphalerite and its parent solution, the remobilized Zn was found consist of about 1/3 to 2/3 of the total Zn in the fluid that formed the conduit samples. Our study suggests that late-stage subsurface hydrothermal remobilization may release isotopically-light Zn to the ocean, and that this process may be common along mid-ocean ridges, thus increasing the size of the previously identified isotopically light Zn sink in the ocean.
Keywords: Hydrothermal activity; Mid ocean ridge; Subsurface remobilization; Zinc isotopic mass balance

Exploratory Research on Key Technology of Human-Computer Interactive 2.5-Minute Fast Digital Early Warning for Mild Cognitive Impairment - Li, Nan; Yang, Xiaotong; Du, Wencai; Ogihara, Atsushi; Zhou, Siyu; Ma, Xiaowen; Wang, Yujia; Li, Shuwu; Li, Kai (Computational Intelligence and Neuroscience, 2022)
Objective. As the preclinical stage of Alzheimer’s disease (AD), Mild Cognitive Impairment (MCI) is characterized by hidden onset, which is difficult to detect early. Traditional neuropsychological scales are main tools used for assessing MCI. However, due to its strong subjectivity and the influence of many factors such as subjects’ educational background, language and hearing ability, and time cost, its accuracy as the standard of early screening is low. Therefore, the purpose of this paper is to propose a new key technology of fast digital early warning for MCI based on eye movement objective data analysis. Methodology. Firstly, four exploratory indexes (test durations, correlation degree, lengths of gaze trajectory, and drift rate) of MCI early warning are determined based on the relevant literature research and semistructured expert interview; secondly, the eye movement state is captured based on the eye tracker to realize the data extraction of four exploratory indexes. On this basis, the human-computer interactive 2.5-minute fast digital early warning paradigm for MCI is designed; thirdly, the rationality of the four early warning indexes proposed in this paper and their early warning effectiveness on MCI are verified. Results. Through the small sample test of human-computer interactive 2.5 fast digital early warning paradigm for MCI conducted by 32 elderly people aged 70–90 in a medical institution in Hangzhou, the two indexes of “correlation degree” and “drift rate” with statistical differences are selected. The experiment results show that AUC of this MCI early warning paradigm is 0.824. Conclusion. The key technology of human-computer interactive 2.5 fast digital early warning for MCI proposed in this paper overcomes the limitations of the existing MCI early warning tools, such as low objectification level, high dependence on professional doctors, long test time, requiring high educational level, and so on. The experiment results show that the early warning technology, as a new generation of objective and effective digital early warning tool, can realize 2.5-minute fast and high-precision preliminary screening and early warning for MCI in the elderly.

An exploration of building up the quality of parent-child relationship in residential childcare in Macao - Leong, On Na Ribeiro; Liu, Shu-Wen (Asian Social Work and Policy Review, 2022)
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/aswp.12252

Using Machine Learning Methods to Forecast Air Quality: A Case Study in Macao - Lei, Thomas M. T.; Siu, Shirley W. I.; Monjardino, Joana; Mendes, Luisa; Ferreira, Francisco (Atmosphere, 2022)
Despite the levels of air pollution in Macao continuing to improve over recent years, there are still days with high-pollution episodes that cause great health concerns to the local community. Therefore, it is very important to accurately forecast air quality in Macao. Machine learning methods such as random forest (RF), gradient boosting (GB), support vector regression (SVR), and multiple linear regression (MLR) were applied to predict the levels of particulate matter (PM10 and PM2.5) concentrations in Macao. The forecast models were built and trained using the meteorological and air quality data from 2013 to 2018, and the air quality data from 2019 to 2021 were used for validation. Our results show that there is no significant difference between the performance of the four methods in predicting the air quality data for 2019 (before the COVID-19 pandemic) and 2021 (the new normal period). However, RF performed significantly better than the other methods for 2020 (amid the pandemic) with a higher coefficient of determination (R2) and lower RMSE, MAE, and BIAS. The reduced performance of the statistical MLR and other ML models was presumably due to the unprecedented low levels of PM10 and PM2.5 concentrations in 2020. Therefore, this study suggests that RF is the most reliable prediction method for pollutant concentrations, especially in the event of drastic air quality changes due to unexpected circumstances, such as a lockdown caused by a widespread infectious disease.
0 citations (Crossref) [2022-09-21] Number: 9 Publisher: Multidisciplinary Digital Publishing Institute
Keywords: COVID-19; air pollution; air quality; air quality forecast; gradient boosting; multiple linear regression; random forest; support vector regression

Minimising Maximum Illud: Early Resistance to Missionary Inculturation in China - Law, Cyril Jerome (Orientis Aura: Macau Perspectives in Religious Studies, 2022)
Section: Articles

An Attempt to Examine Digital Native and Digital Immigrant Macau Graphic Designers' Perceptions of Adopting Generative Design - Lau, Ching Man; Caires, Carlos Sena (International Journal of Creative Interfaces and Computer Graphics (IJCICG), 2022)
The manifestation of generating digital visuals through an algorithm is gaining worldwide attention in the graphic design industry. It is a new form of computing that visualizes data input by the designer or collected in the physical environment and turns them into artwork. The generative design of...
Publisher: IGI Global

Noise-induced hearing loss correlates with inner ear hair cell decrease in larval zebrafish - Lara, Rafael A.; Breitzler, Lukas; Lau, Ieng Hou; Gordillo-Martinez, Flora; Chen, Fangyi; Fonseca, Paulo J.; Bass, Andrew H.; Vasconcelos, Raquel O. (Journal of Experimental Biology, 2022)
Anthropogenic noise can be hazardous for the auditory system and wellbeing of animals, including humans. However, very limited information is known on how this global environmental pollutant affects auditory function and inner ear sensory receptors in early ontogeny. The zebrafish (Danio rerio) is a valuable model in hearing research, including investigations of developmental processes of the vertebrate inner ear. We tested the effects of chronic exposure to white noise in larval zebrafish on inner ear saccular sensitivity and morphology at 3 and 5 days post-fertilization (dpf), as well as on auditory-evoked swimming responses using the prepulse inhibition (PPI) paradigm at 5 dpf. Noise-exposed larvae showed a significant increase in microphonic potential thresholds at low frequencies, 100 and 200 Hz, while the PPI revealed a hypersensitization effect and a similar threshold shift at 200 Hz. Auditory sensitivity changes were accompanied by a decrease in saccular hair cell number and epithelium area. In aggregate, the results reveal noise-induced effects on inner ear structure–function in a larval fish paralleled by a decrease in auditory-evoked sensorimotor responses. More broadly, this study highlights the importance of investigating the impact of environmental noise on early development of sensory and behavioural responsiveness to acoustic stimuli.
2 citations (Crossref) [2022-09-21]

The Influence of Society on the Behavioral Intention to Use a Technology: Evidence from the Battery Electric Vehicles Domain - Lampo, Alessandro; Silva, Susana C.; Duarte, Paulo (International Journal of Business Excellence, 2022)

Self-Efficacy, Stress and Job Satisfaction among Pre-Service, Novice and Experienced English Teachers: A Study of their Occupational Health - Lam, Stacy; Kuok, A. C. H.; Sze, Tat Ming (Health Psychology Report, 2022)
Background This study aimed to investigate English teachers’ self-efficacy for student engagement, classroom management, instructional strategies and literacy instruction, as well as to discover teacher stress and job satisfaction can play a role in interfering their occupational health (in terms of self-efficacy). In addition, this is one of the first studies to understand the differences in self-efficacy among pre-service, novice and experienced in-service teachers in a Chinese society, where English is positioned as a foreign language. Participants and procedure 271 English teachers (90 pre-service, 181 in-service) with mean teaching experience of 5.57 months for per-service, and 98.51 months for in-service were participated in this quantitative research study, as the targets were not be able to approach randomly, the English teachers were approaching individually though referral sampling, informing that the purpose of the study and receive their consent. Results It discovered both pre-service and novice in-service teachers posses lowest self-efficacy. Moreover, teachers’ stress from classroom predicted their self-efficacy for student engagement and classroom management negatively. On the other hand, teachers’ job satisfaction predicts their self-efficacy for student engagement, instructional strategies and literacy instruction positively. Conclusions Implications (based on the findings) are discussed in order to provide insights for for schools and education departments to strengthen the teachers’ capability of teaching and their occupational health.
0 citations (Crossref) [2022-10-30]

A positivist approach to work engagement: moderating effects of perceived organizational support - Kuok, A. C. H; Taormina, Robert J. (Dynamic Relationships Management Journal, 2022)
0 citations (Crossref) [2022-10-30]

Emotional Intelligence, Work Satisfaction, and Affective Commitment: An Occupational Health Study of Social Workers - Kuok, A. C. H. (Journal of Work and Organizational Psychology, 2022)
Social workers’ work engagement and burnout were tested in relation to (a) personal variable, i.e., emotional intelligence; (b) organizational variables, i.e., work satisfaction and affective commitment. Regressions revealed emotional intelligence - controlling self – negatively predicted depersonalization and reduced personal accomplishment and positively predicted three facets of work engagement. Emotional intelligence - understanding others – was a negative predictor of reduced personal accomplishment. In addition, work satisfaction negatively predicted three components of burnout and positively predicted emotional work engagement. Affective commitment was a positive predictor of three facets of work engagement and negatively predicted reduced personal accomplishment. Implications for management are discussed.
Company: Colegio Oficial de Psicologos de Madrid (copmadrid) Distributor: Colegio Oficial de Psicologos de Madrid (copmadrid) Institution: Colegio Oficial de Psicologos de Madrid (copmadrid) Label: Colegio Oficial de Psicologos de Madrid (copmadrid) Publisher: Colegio Oficial de Psicologos de Madrid Section: research-article

Quality of life during the pandemic: a cross sectional study about attitude, individual perspective and behavior change affecting general population in daily life - Khatoon, F.; Kumar, M.; Khalid, A. A.; Alshammari, A. D.; Khan, F.; Alshammari, R. D.; Balouch, Z.; Verma, D.; Mishra, P.; Abotaleb, M.; Makarovskikh, T.; El-kenawy, E. M.; et al. (2022)
Quality of life in general population before and during pandemic is topic need to be address by researcher in terms of mobility, self-care, usual activities, pain/discomfort and anxiety/depression. The study was carried out among Saudi population. Data were collected from general population using questionnaire during the period from 22 August 2021 to 10th January 2022. As a result, total 214 participants have included in this study. Among them prevalent age group include 40 years (n= 63, 29.4%) shadowed by the age group 25-35 (n= 61, 28.5%) while above 60 years group were least frequent (n= 1, 0.5%). On questioning the applicants whether they were satisfied with their health and how would they rate their quality of life, their answers were as follows: yes, or satisfied (n= 86, 40.2%), very Satisfied (n= 102, 47.7%) Dissatisfied (n= 11, 5.1%) and neither satisfied nor dissatisfied (n= 15, 7%). Due to pandemic, they were rate quality of life very good (n= 94, 43.9%), good (n= 63, 29.4 %) poor (n= 5, 2.3 %) and neither good and nor poor (n= 52, 24.3 %). During pandemic 96 participants feel no change in their weight but 110 participants respond that there is increase in coffee intake during the pandemic. Similarly increased in smoking habits and decrease rate in social activities (n=119,41.4%). The psychosomatic well-being of people has been interrupted by disturbing their social activities during pandemic.
Publisher: IET Digital Library

How can environmental conditions influence dicofol genotoxicity on the edible Asiatic clam, Meretrix meretrix? - Ivorra, Lucia; Cruzeiro, Catarina; Ramos, Alice; Tagulao, Karen; Cardoso, Patricia G. (Environmental Pollution, 2022)
Genotoxic effects of dicofol on the edible clam Meretrix meretrix were investigated through a mesocosm experiment. Individuals of M. meretrix, were exposed to environmental concentration (D1 = 50 ng/L) and supra-environmental concentration (D2 = 500 ng/L) of dicofol for 15 days, followed by the same depuration period. DNA damage (i.e., strand breaks and alkali-labile sites) was evaluated at day 1, 7 and 15, during uptake and depuration, using Comet assay (alkaline version) and nuclear abnormalities (NAs) as genotoxicity biomarkers. The protective effects of dicofol against DNA damage induced by ex vivo hydrogen peroxide (H2O2) exposure were also assessed. Comet assay results revealed no significant DNA damages under dicofol exposure, indicating 1) apparent lack of genotoxicity of dicofol to the tested conditions and/or 2) resistance of the animals due to optimal adaptation to stress conditions. Moreover, ex vivo H2O2 exposure showed an increase in the DNA damage in all the treatments without significant differences between them. However, considering only the DNA damage induced by H2O2 during uptake phase, D1 animals had significantly lower DNA damage than those from other treatments, revealing higher protection against a second stressor. NAs data showed a decrease in the % of cells with polymorphic, kidney shape, notched or lobbed nucleus, along the experiment. The combination of these results supports the idea that the clams used in the experiment were probably collected from a stressful environment (in this case Pearl River Delta region) which could have triggered some degree of adaptation to those environmental conditions, explaining the lack of DNA damages and highlighting the importance of organisms’ origin and the conditions that they were exposed during their lives.
Keywords: Bivalves; Comet assay; DNA damage; Nuclear abnormalities; Organochlorine pesticides

Examining the impact of behavioral factors on the intention of adopting E-government services: An empirical study on the hard-to-reach groups in Macao SAR, China - Iong, Kit Yeng; Phillips, Jenny O. L. (Technology in Society, 2022)
In government studies, electronic government has become a hot topic in recent decades. Many scholars believe that soon, the government might not be able to operate smoothly without the help of ICTs as the Internet has been overwhelming people's daily lives already. In analyzing people's behavioral factors towards adopting e-government services, most studies targeted the adult population, while those in the hard-to-reach groups are minimal. This study was designed especially to understand the behavioral factors of the younger generation aged between 18 and 24 and the senior citizens above 60 on their adoption of e-government services in Macao SAR. Sixteen in-depth interviews were conducted based on the semi-structured interview questions developed from the prior literature on the Theory of Planned Behavior and e-government studies. Six significant findings are yielded, which could serve as an important reference for policymakers designing e-government policy and promoting its implementation strategy. These behavioral factors also contribute empirical data to support the theoretical framework of TPB in the context of Macao SAR e-government services.
0 citations (Crossref) [2022-09-21]
Keywords: Electronic government; Hard-to-reach groups; In-depth interviews; The theory of planned behavior

Design Explorations for 3D-Printed Modular Markers for eXtended-Reality Tangible User Interfaces: - Iok Fong, Chau; Cardoso, Jorge C. S.; Estadieu, Gerald Vincent (International Journal of Creative Interfaces and Computer Graphics, 2022)
Various materials, objects, and sensors have been explored earlier for creating tangible user interfaces (TUIs). However, there is little work on 3D-printed TUIs based on visual markers for smartphone-based extended reality (XR) experiences. The combination of visual markers and smartphones results in cheap, accessible XR systems within reach of many people. Combined with 3D printing, it could foster do-it-yourself (DIY) projects for XR experiences, which may further expand and open-up possibilities for accessible and tangible interaction. This work explores the design space of modular 3D-printed tangibles for smartphone-based XR. The authors report the design exploration process, provide several interactive 3D-printed markers, and reflect on the resulting possibilities.
0 citations (Crossref) [2022-10-27]

Constructing an aesthetic discourse: Aesthetic education where Daoism meets postmodernism - Ho, Ka Lee Carrie (Education Inquiry, 2022)
Despite the prevalence of aesthetic education as one of the main developmental objectives in curricular worldwide, the mainstream philosophical discourse on its definition is predominately framed by western philosophy due to a paucity of cross-cultural studies on the subject. The article aims to achieve a contemporary understanding of aesthetic education from both the Chinese and Western aesthetic perspectives. Through the lens of postmodernism, the relationship between Daoist aesthetics and the western postmodern aesthetic perspectives, particularly the Deleuzian concept of rhizome, is identified. Both aesthetic perspectives concern de-authorship and promote self-consciousness/self-awareness. The study reconceptualises the functions of aesthetic education with the Chinese aesthetic philosophy that promotes the nurture of better people through benevolence.
Publisher: Routledge _eprint: https://doi.org/10.1080/20004508.2020.1831286
Keywords: Aesthetic experiences; Daoism; Deleuze; aesthetic environments; rhizome

Attentive recurrent adversarial domain adaptation with Top-k pseudo-labeling for time series classification - He, Qi-Qiao; Siu, Shirley Weng In; Si, Yain-Whar (Applied Intelligence, 2022)
The key challenge of Unsupervised Domain Adaptation (UDA) for analyzing time series data is to learn domain-invariant representations by capturing complex temporal dependencies. In addition, existing unsupervised domain adaptation methods for time series data are designed to align marginal distribution between source and target domains. However, existing UDA methods (e.g. R-DANN Purushotham et al. (2017), VRADA Purushotham et al. (2017), CoDATS Wilson et al. (2020)) neglect the conditional distribution discrepancy between two domains, leading to misclassification of the target domain. Therefore, to learn domain-invariant representations by capturing the temporal dependencies and to reduce the conditional distribution discrepancy between two domains, a novel Attentive Recurrent Adversarial Domain Adaptation with Top-k time series pseudo-labeling method called ARADA-TK is proposed in this paper. In the experiments, our proposed method was compared with the state-of-the-art UDA methods (R-DANN, VRADA and CoDATS). Experimental results on four benchmark datasets revealed that ARADA-TK achieves superior classification accuracy when it is compared to the competing methods.
Keywords: Adversarial training; Attentive; Domain adaptation; Pseudo-labeling; Time series classification

Instance-based deep transfer learning with attention for stock movement prediction - He, Qi-Qiao; Siu, Shirley Weng In; Si, Yain-Whar (Applied Intelligence, 2022)
Stock movement prediction is one of the most challenging problems in time series analysis due to the stochastic nature of financial markets. In recent years, a plethora of statistical methods and machine learning algorithms were proposed for stock movement prediction. Specifically, deep learning models are increasingly applied for the prediction of stock movement. The success of deep learning models relies on the assumption that massive training data are available. However, this assumption is impractical for stock movement prediction. In stock markets, a large number of stocks do not have enough historical data, especially for the companies which underwent initial public offering in recent years. In these situations, the accuracy of deep learning models to predict the stock movement could be affected. To address this problem, in this paper, we propose novel instance-based deep transfer learning models with attention mechanism. In the experiments, we compare our proposed methods with state-of-the-art prediction models. Experimental results on three public datasets reveal that our proposed methods significantly improve the performance of deep learning models when limited training data are available.
0 citations (Crossref) [2022-09-21]
Keywords: Attention mechanism; Deep transfer learning; Instance-based; Stock movement prediction

Temporary transnational labour mobility and gendered individualization in Europe - Harsløf, Ivan; Zuev, Dennis (Mobilities, 2022)
In a context of a new transnational division of labour, temporary international labour mobility is on the rise in Europe. In particular, recent decades have seen considerably more women seeking work experience abroad. Observers have been concerned with how such mobility is related to individualization, and in particular how it may challenge collective institutions, communities and families. The aim of this study is to explore such issues among women and men with international work experience. Using data from European Social Survey, the paper investigates previously mobile workers in terms of their current working and living conditions. Across genders, we consider different forms of individualization that may be associated with transnational labour mobility. While both women and men with transnational work experience generally feature strong strategic individualization, this is most pronounced among men. Hence, men's mobility is among other things associated with increased autonomy in working life, while – in contrast to women – it does not seem to hamper their integration in the sphere of social reproduction.
0 citations (Crossref) [2022-11-10] Publisher: Routledge _eprint: https://doi.org/10.1080/17450101.2022.2092417
Keywords: Europe; Temporary labour mobility; individualization; sphere of production; sphere of social reproduction; transnational division of labour

A contribution to Paulo Freire’s theory and practice: The ‘Cultural Extension Service/University of Recife’ (1962–64) - Gerhardt, Heinz Peter (Educational Philosophy and Theory, 2022)
This contribution to the special issue is an historical account of Paulo Freire’s pedagogical and administrative praxis before his forced exile in 1964. It relies on interviews collected during a field trip in 1976, a conversation with Paulo Freire in Geneva one year later and on the secondary literature up to date. Being the head of the first Extension Service of a major Brazilian university in the early 1960s gave Freire and his collaborators the space and time to experiment with the today world famous literacy method bearing his name. The concept of ‘Field of Cultural Production’ (Bourdieu) is used to elucidate better Freire and his team’s avant-gardist production within the spaces opened up by Brazil’s popular movements in the early sixties. The contribution shows how the ‘Paulo Freire System’ developed in the praxis of a cultural movement and received its academic consecration in an incremental and eclectic style.
Publisher: Routledge _eprint: https://doi.org/10.1080/00131857.2022.2129007
Keywords: Bourdieu; Brazil; Paulo Freire; University of Recife; extension service; literacy

Belt and Road Initiatives: implications for China’s internationalisation of tertiary-level education - Ge, Yun; Ho, Kong Chong (Educational Research and Evaluation, 2022)
Since the launch of the One Belt and One Road Initiative (BRI) in 2013, the internationalisation of China’s tertiary education has entered a new stage. Central to the BRI is investment and strategic planning for talent cultivation, knowledge production, and transmission. This paper explains how the BRI redirects, reinforces, and intensifies China’s strategic planning and actions for internationalising its education. It adopts a policy analysis approach and reviews three key aspects of development and shifting emphasis of internationalisation under the impact of the BRI: international education networks along the Six BRI Economic Corridors, vocational colleges as new players in international education, and promotion of the Chinese language as a new global language. The analysis captures an important moment in which international education processes are being visibly altered through China’s strategies to take the lead in economic globalisation and to compete for a central place in the world via the BRI.
0 citations (Crossref) [2022-09-21] Publisher: Routledge _eprint: https://doi.org/10.1080/13803611.2022.2041858
Keywords: Belt and Road Initiatives; Chinese language; Internationalisation of higher education; vocational education

Internationalisation of higher education: new players in a changing scene - Ge, Yun (Educational Research and Evaluation, 2022)
0 citations (Crossref) [2022-09-21] Publisher: Routledge _eprint: https://doi.org/10.1080/13803611.2022.2041850

From Maximum Illud 1919 to the First National Synod Primum Concilium Sinensis 1924 in Shanghai: Historical & Theological Perspectives - Gassner, Franz (Orientis Aura: Macau Perspectives in Religious Studies, 2022)
Section: Articles

Learning God’s Mercy: Spiritual Transformation According to Hos 11:8 - Gassner, Franz (The Journal of the Macau Ricci Institute, 2022)
A growing focus on God’s mercy and forgiveness emerged in the wake of the recent Pontificates of John Paul II, Benedict XVI, and Francis. Our time with its multiple crises cries for healing, forgiveness, and the experience of God’s mercy. In social, political, and global terms, humanity craves for “lasting peace, born of the marriage of justice and mercy” (John Paul II, 2001, no. 15). The experience of God’s forgiveness, merciful healing and new life has been expressed many times in the Bible. But, theologically, it has never been formulated as directly as in Hosea 11:8, when God’s own heart becomes “turned over”, “converted” following the blaze of his own overwhelming compassion, paving the way for a fundamental spiritual transformation, rooted in forgiveness and mercy, that opens wellsprings of dignity, healing, and new life for all.

Religious Vows in their Mystic and Prophetic Dimensions - Gallares, Judette (Religious Life Asia, 2022)

A Critical Look at Blockchain-Interactive Generative Art - Farinha, Daniel Filipe (International Journal of Creative Interfaces and Computer Graphics, 2022)
Artists are increasingly using blockchain as a tool for trading digital artwork as non-fungible tokens (NFTs); however, some are also beginning to experiment with the blockchain as a medium for generative art, using it as a seed for a generative process or to continuously modify an evolving piece. This paper surveys, reviews, and classifies the state-of-the-art in blockchain-interactive NFTs and presents a liberal-arts critique of the opportunities and threats posed by this technology, whilst addressing existing criticism on the broader topic of art-related NFTs. The paper examines some of the most experimental pieces minted on the Hic et Nunc (HEN) and Teia NFT marketplaces, for which a purpose-built research tool was developed. The survey reveals some reliance on centralised infrastructure, namely blockchain indexers, placing undesired trust on third parties which undermines the potential longevity of the artwork. The paper concludes with recommendations for artists and NFT platform designers for developing more resilient and economically sustainable architectures.
Keywords: Art Preservation; Blockchain; Crypto Art; Dynamic NFT; Generative Art; Non-Fungible Token; Provenance

Trace-element compositions of sulfides from inactive Tianzuo hydrothermal field, Southwest Indian Ridge: Implications for ultramafic rocks hosting mineralization - Ding, Teng; Wang, Jia; Tao, Chunhui; Dias, Ágata Alveirinho; Liang, Jin; Wang, Yuan; Chen, Jie; Wu, Bin; Huang, Hui (Ore Geology Reviews, 2022)
The recently explored inactive Tianzuo hydrothermal field, in the amagmatic segment of the ultraslow-spreading Southwest Indian Ridge (SWIR), is closely associated with detachment faults. In this site, sulfide minerals are hosted by serpentine-bearing ultramafic rocks and include high-temperature (isocubanite, sphalerite, and minor pyrrhotite) and low-temperature (pyrite I, marcasite, pyrite II, and covellite) phases. In this study, trace-element concentrations of isocubanite and pyrite II were used to elucidate mineralization processes in ultramafic rocks hosting sulfides. Results show that isocubanite is enriched in metals such as Cu, Co, Sn, Te, Zn, Se, Pb, Bi, Cd, Ag, In, and Mn, and pyrite II is enriched in Mo and Tl. The marked enrichment in Te, Cu, Co, and In in isocubanite (compared with Se, Zn, Ni, and Sn, respectively) is most likely due to the contribution of magmatic fluids from gabbroic intrusions beneath the hydrothermal field. The intrusion of gabbroic magmas would have enhanced serpentinization reactions and provided a relatively oxidizing environment through the dissolution of anhydrite precipitated previously in the reaction zone, within high temperature and low pH conditions. This might have facilitated the extraction of metals by initial hydrothermal fluids, leading to the general enrichment of most metals in isocubanite. Metals in pyrite II have compositions similar to those of isocubanite, except for strong depletion in magmatically derived Te, Cu, Co, and In. This means that serpentinization processes had a dominating role in pyrite II precipitation as well. The enrichment of pyrite II in Mo and Tl is also indicative of seawater contribution in its composition. The study concludes that serpentinization reactions contribute effectively both to high- and low-temperature sulfide mineralization at Tianzuo hydrothermal field, with gabbroic intrusions further promoting high-temperature sulfide mineralization, providing additional metals, fluids and heat. In contrast, low-temperature sulfide mineralization occurred during the cooling of gabbroic intrusions, with decreasing rates of serpentinization reactions and a significant influence of seawater.
Keywords: SWIR; Serpentinization; Sulfide; Tianzuo; Trace-element; Ultramafic rocks

An Exploratory Study on the Possibility of Harmonizing Investment Protection Regimes within the OHADA Zone - Diakité, A. D.; Thiam, A. B. (Transnational Dispute Management (TDM), 2022)
Abstract With its large population and natural resources, Africa needs investors who can sustain its development. At the same time, foreign investors expect returns on their investments. In ...
Publisher: Maris BV

The evolutionary argument against naturalism: a Wittgensteinian response - DeVito, Michael; McNabb, Tyler (International Journal for Philosophy of Religion, 2022)
In this essay, we put forth a novel solution to Plantinga’s Evolutionary Argument Against Naturalism, utilizing recent work done by Duncan Pritchard on radical skepticism. Key to the success of Plantinga’s argument is the doubting of the reliability of one’s cognitive faculties. We argue (viz. Pritchard and Wittgenstein) that the reliability of one’s cognitive faculties constitutes a hinge commitment, thus is exempt from rational evaluation. In turn, the naturalist who endorses hinge epistemology can deny the key premise in Plantinga’s argument and avoid the dilemma posed on belief in the conjunction of naturalism and evolution.
0 citations (Crossref) [2022-09-21]

Exploring the participation and agency of students with special education needs in a Macau-Chinese secondary school - Correia, Ana M.; Forlin, Chris; Sio, Eva (Journal of Research in Special Educational Needs, 2022)
The research explores the perceptions of five secondary school students with special education needs (SEN) about their participation in learning, group membership, and agency within an inclusive school in Macau SAR. This goal is achieved by using students' voices documented in open-ended interviews and is underpinned by the conceptual framework of heutagogy. The aim is to shed light on students' perceptions on school effectiveness in supporting their needs through successful participation and agentic possibilities. Findings showed that students were more prone to social rejection and being isolated or bullied than their peers. They were struggling to feel included or participate, their needs were only partially being met, and they had few opportunities to exert influence on their educational trajectories. Recommendations are provided to assist educators and schools in enhancing students with SEN to connect to the learning process and community, with the provision of appropriate learning adjustments and more active approaches to ensure their acceptance by mainstream students, including the formation of coaching peers to assist in developing social and academic skills under teacher's scaffolding practices. This study highlights the contribution of the heutagogical perspective to advance research on the participation and agency of students with SEN in mainstream schools.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/1471-3802.12566
Keywords: Macau SAR; Special education needs; agency; disability; inclusive education; participation; students' voice

An Integrated Learning Platform Focusing on STEAM and Collaborative Modules for Macau - Cheng, Un Man; Martins de Abreu, F. (International Journal of Creative Interfaces and Computer Graphics (IJCICG), 2022)
In Macau, the effectiveness of traditional classroom learning is questioned as the problem is discovered by the changes in technology advances, social media, and the varieties of learning methods. Learning experiences, interests, discoveries, and creativity development are considered essential to ac...
Publisher: IGI Global

A Neuropeptide Y/F-like Polypeptide Derived from the Transcriptome of Turbinaria peltata Suppresses LPS-Induced Astrocytic Inflammation - Chen, Qian; Liang, Zirong; Yue, Qian; Wang, Xiufen; Siu, Shirley Weng In; Pui-Man Hoi, Maggie; Lee, Simon Ming-Yuen (Journal of Natural Products, 2022)
Neuropeptides are a group of neuronal signaling molecules that regulate physiological and behavioral processes in animals. Here, we used in silico mining to predict the polypeptide composition of available transcriptomic data of Turbinaria peltata. In total, 118 transcripts encoding putative peptide precursors were discovered. One neuropeptide Y/F-like peptide, named TpNPY, was identified and selected for in silico structural, in silico binding, and pharmacological studies. In our study, the anti-inflammation effect of TpNPY was evaluated using an LPS-stimulated C8-D1A astrocyte cell model. Our results demonstrated that TpNPY, at 0.75–3 μM, inhibited LPS-induced NO production and reduced the expression of iNOS in a dose-dependent manner. Furthermore, TpNPY reduced the secretion of proinflammatory cytokines. Additionally, treatment with TpNPY reduced LPS-mediated elevation of ROS production and the intracellular calcium concentration. Further investigation revealed that TpNPY downregulated the IKK/IκB/NF-κB signaling pathway and inhibited expression of the NLRP3 inflammasome. Through molecular docking and using an NPY receptor antagonist, TpNPY was shown to have the ability to interact with the NPY Y1 receptor. On the basis of these findings, we concluded that TpNPY might prevent LPS-induced injury in astrocytes through activation of the NPY-Y1R.
0 citations (Crossref) [2022-09-21] Publisher: American Chemical Society

CCAAT/Enhancer-Binding Protein Alpha Is a Novel Regulator of Vascular Smooth Muscle Cell Osteochondrogenic Transition and Vascular Calcification - Chen, Pengyuan; Hong, Wanzi; Chen, Ziying; Gordillo-Martinez, Flora; Wang, Siying; Fan, Hualin; Liu, Yuanhui; Dai, Yining; Wang, Bo; Jiang, Lei; Yu, Hongjiao; He, PengCheng (Frontiers in Physiology, 2022)
AimsVascular calcification is a common clinical complication of chronic kidney disease (CKD), atherosclerosis (AS), and diabetes, which is associated with increased cardiovascular morbidity and mortality in patients. The transdifferentiation of vascular smooth muscle cells (VSMCs) to an osteochondrogenic phenotype is a crucial step during vascular calcification. The transcription factor CCAAT/enhancer-binding protein alpha (C/EBPα) plays an important role in regulating cell proliferation and differentiation, but whether it regulates the calcification of arteries and VSMCs remains unclear. Therefore, this study aims to understand the role of C/EBPα in the regulation of vascular calcification.Methods and ResultsBoth mRNA and protein expression levels of C/EBPα were significantly increased in calcified arteries from mice treated with a high dose of vitamin D3 (vD3). Upregulation of C/EBPα was also observed in the high phosphate- and calcium-induced VSMC calcification process. The siRNA-mediated knockdown of C/EBPα significantly attenuated VSMC calcification in vitro. Moreover, C/EBPα depletion in VSMCs significantly reduced the mRNA expression of the osteochondrogenic genes, e.g., sex-determining region Y-box 9 (Sox9). C/EBPα overexpression can induce SOX9 overexpression. Similar changes in the protein expression of SOX9 were also observed in VSMCs after C/EBPα depletion or overexpression. In addition, silencing of Sox9 expression significantly inhibited the phosphate- and calcium-induced VSMC calcification in vitro.ConclusionFindings in this study indicate that C/EBPα is a key regulator of the osteochondrogenic transdifferentiation of VSMCs and vascular calcification, which may represent a novel therapeutic target for vascular calcification.

Anti-epileptic Kunitz-like peptides discovered in the branching coral Acropora digitifera through transcriptomic analysis - Chen, Hanbin; Siu, Shirley Weng In; Wong, Clarence Tsun Ting; Qiu, Jianwen; Cheung, Alex Kwok-Kuen; Lee, Simon Ming Yuen (Archives of Toxicology, 2022)
Approximately 50 million people are suffering from epilepsy worldwide. Corals have been used for treating epilepsy in traditional Chinese medicine, but the mechanism of this treatment is unknown. In this study, we analyzed the transcriptome of the branching coral Acropora digitifera and obtained its Kyoto Encyclopedia of Genes and Genomes (KEGG), EuKaryotic Orthologous Groups (KOG) and Gene Ontology (GO) annotation. Combined with multiple sequence alignment and phylogenetic analysis, we discovered three polypeptides, we named them AdKuz1, AdKuz2 and AdKuz3, from A. digitifera that showed a close relationship to Kunitz-type peptides. Molecular docking and molecular dynamics simulation indicated that AdKuz1 to 3 could interact with GABAA receptor but AdKuz2–GABAA remained more stable than others. The biological experiments showed that AdKuz1 and AdKuz2 exhibited an anti-inflammatory effect by decreasing the aberrant level of nitric oxide (NO), IL-6, TNF-α and IL-1β induced by LPS in BV-2 cells. In addition, the pentylenetetrazol (PTZ)-induced epileptic effect on zebrafish was remarkably suppressed by AdKuz1 and AdKuz2. AdKuz2 particularly showed superior anti-epileptic effects compared to the other two peptides. Furthermore, AdKuz2 significantly decreased the expression of c-fos and npas4a, which were up-regulated by PTZ treatment. In addition, AdKuz2 reduced the synthesis of glutamate and enhanced the biosynthesis of gamma-aminobutyric acid (GABA). In conclusion, the results indicated that AdKuz2 may affect the synthesis of glutamate and GABA and enhance the activity of the GABAA receptor to inhibit the symptoms of epilepsy. We believe, AdKuz2 could be a promising anti-epileptic agent and its mechanism of action should be further investigated.
0 citations (Crossref) [2022-09-21]
Keywords: Anti-epileptic; GABAA; Kunitz peptide; Transcriptome

How social media affects the purchase intentions of female consumers in Macao - watching beauty and cosmetics product experience videos on YouTube - Chan, Velda; Silva, Susana C.; Lampo, Alessandro (Revista Gestão em Análise, 2022)
YouTube has become increasingly popular for marketing purposes. As corporate and user-generated content is widely available on this platform, beauty-related professionals need to understand how to create videos that make their products more appealing and stand out from the clutter. In this study, we examine four factors (i.e., perceived usefulness of the information, perceived credibility of the information, attitude toward the purchase, and perceived video characteristics) that affect the purchase intentions of female consumers. After viewing beauty-related videos, a sample of 204 female consumers was analyzed by structural equation modeling. The findings showed that videos with more views, likes, and comments tend to have a greater effect on the respondents' intentions to purchase. Also, the factors of perceived usefulness of the information, perceived credibility of the information, and attitude toward the purchase exhibited a significant effect on the intention to buy beauty-related products. The result showed that perceived video characteristics (such as quality and visuals) did not significantly influence the purchase intention, however, there is evidence that this factor should not be ignored by content creators. Finally, our research provides insights, strategies, and future directions for industry practitioners and marketers.
Number: 3
Keywords: YouTube beauty products; YouTube marketing; beauty and cosmetics marketing; purchase intention

To follow or overcome our nature? - Cai, Yulin (GREGORIANUM, 2022)
The doctrine of original sin gives people the impression that the goodness of human nature is under-evaluated in the Christian theological tradition. The Chinese philosopher Mencius is famous for his teaching on the goodness of human nature. Reading Mencius and Thomas Aquinas side by side, this article argues that the Mencian teaching on human nature brings us to affirm the goodness of human nature by recovering the significance of the image of God for the Christian doctrine of human nature. If we seek the goodness of human nature in the possibilities to become good, it is natural to see that even in the fallen state the possibilities of becoming like God remain in human nature imprinted with the image of God. It is open to the culmination of a gradual progression to its perfection.

Modulações em português de imagens, experiências e estesias orientais: revisão das razões do fascínio de alguma dicção poética chinesa e japonesa como utopia da poesia - Borges, Vera (Alea: Estudos Neolatinos, 2022)
Resumo O fascínio do Ocidente pela dicção poética oriental está atestado em várias latitudes e línguas, e resultou numa profícua produção na área da poesia. Sabe-se que a reinvenção da poesia chinesa da autoria de Pound, em grande medida na origem da sua proposta de revolução do idioma poético, nas primeiras décadas do séc. XX, assentou, na verdade, numa falácia; numa concepção errada da natureza da escrita chinesa (e japonesa) como essencialmente pictográfica e ideogramática, na base de propriedades expressivas reconhecidas na poesia que resultariam numa particular eficácia na apreensão e tradução do real. Pessanha enaltece, em termos similares aos da exaltação poundiana, a escrita da poesia chinesa clássica. Interessa-nos rever alguns inventários dos traços da dicção poética chinesa e japonesa que explicam que ela seja tomada como metonímia e metáfora da poesia, ou como meta e utopia da poesia, para perceber o que terá levado autores muito díspares a tentar a mão nos haikus, processo em que sondaremos algumas formulações poéticas em língua portuguesa. Consideramos também que esse fascínio por uma (sonhada) origem da dicção poética, quando cruzada com o habitar (não metafórico, neste caso) do pequenino enclave de Macau, de autores que nele lançaram raízes, resultou em alguns exercícios poéticos particularmente felizes e singulares. Serão trazidos à colação nesta abordagem poemas de Eugénio de Andrade, Sophia de Mello Breyner Andresen, José Tolentino Mendonça, Yao Feng, Fernanda Dias e Fernando Sales Lopes.
Publisher: Programa de Pos-Graduação em Letras Neolatinas, Faculdade de Letras -UFRJ
Keywords: Macau; Pound; falácia; haiku; poesia; poesia chinesa; trocar de voz

Behavioural and endocrine responses to non-interactive live and video conspecifics in males of the Siamese fighting fish - Alex, Deepa; Cardoso, Sara D; Ramos, Andreia; Gonçalves, David (Current Zoology, 2022)
The physiological mechanisms underlying variation in aggression in fish remain poorly understood. One possibly confounding variable is the lack of standardization in the type of stimuli used to elicit aggression. The presentation of controlled stimuli in videos, a.k.a. video playback, can provide better control of the fight components. However, this technique has produced conflicting results in animal behaviour studies and needs to be carefully validated. For this, a similar response to the video and an equivalent live stimulus needs to be demonstrated. Further, different physiological responses may be triggered by live and video stimuli and it is important to demonstrate that video images elicit appropriate physiological reactions. Here, the behavioural and endocrine response of male Siamese fighting fish Betta splendens to a matched for size conspecific fighting behind a one-way mirror, presented live or through video playback, was compared. The video playback and live stimulus elicited a strong and similar aggressive response by the focal fish, with a fight structure that started with stereotypical threat displays and progressed to overt attacks. Post-fight plasma levels of the androgen 11-ketotestosterone were elevated as compared to controls, regardless of the type of stimuli. Cortisol also increased in response to the video images, as previously described for live fights in this species. These results show that the interactive component of a fight, and its resolution, are not needed to trigger an endocrine response to aggression in this species. The study also demonstrates for the first time in a fish a robust endocrine response to video stimuli and supports the use of this technique for researching aggressive behaviour in B. splendens.

Diversity and Variation in China's Yao Ancient Wood Frame Structures Through Genetic Algorithms: - Afonso, Filipe; Jedenov, Kirill; Januário, Pedro Gomes; Almeida, Paulo (International Journal of Creative Interfaces and Computer Graphics, 2022)
This study, focusing on the China's Yao minority community, investigates the feasibility to create a generative computational method to replicate the diversity of the existing Yao traditional wood buildings, addressing the critical issues currently facing computational design methods, in the attempt to adapt genetic-generative algorithms to the study of local ancient architecture. The project develops a computational tool to generate a network of three-dimensional prototypes, or building structures, derived from traditional wood frame village houses. It studies possible housing structures that illustrate some of the key working methods available in digital systems such as ‘generating' and ‘compositing' taking as a starting point computational strategies oriented towards geometry and where a set of local variables play a decisive role: available local technologies, use of raw materials, and the dimensioning of timber components based on data collected from Yao architecture.